EVALUATION OF RESULTS OF SIMULTANEOUS MYOMECTOMY AND CESAREAN SECTION - A. G. Yaschuk; L. A. Dautova; A. A. Tyurina; A. G. Imelbaeva (Креативная хирургия и онкология)
Introduction. Myoma of the uterus is the most common neoplasm of the female reproductive system. The frequency of combination of uterine fibroids and pregnancy varies from 1.6% to 10.7%, often fibroids occur in pregnant women of late reproductive age. Traditionally, myomectomy during caesarean section was not recommended because of the risk of bleeding and postoperative complications. To assess the safety and feasibility of a one-stage myomectomy in a caesarean section, this study was conducted.Materials and methods. From 2010 to 2015, we examined 260 pregnant women with uterine myoma, who had a cesarean section with a single-stage myomectomy. The data obtained during the survey were compared with the data of 96 women from the control group. We study assessment of intraoperative blood loss, pre- and postoperative hemoglobin levels, duration of hospitalization.Results. Statistically significant differences in intraoperative blood loss, changes in hemoglobin levels and in the duration of hospitalization between the examined groups of women were not revealed. A prognostic model has been developed to assess risk factors for intraoperative blood loss of more than 1000 ml.Conclusion. The size, localization of myomatous nodes are not risk factors for high blood loss in abdominal delivery with a one-stage myomectomy. The factor of risk of hemorrhage is multiple uterine fibroids, whereas the size of myomatous nodes less than 5 cm can be regarded as a protective factor for blood loss. The study showed that a one-stage myomectomy with a caesarean section is safe and can be performed with the surgeon’s experience.